Teaching about venomous animals in two public schools in the municipality of Benjamin Constant - AM - Silva, Daiane Bindá; Lopes, Alcinei Pereira; Pinto, Márcia Nascimento; Acioli, Agno Nonato Serrão; Brandão, Eliel Guimarães; Montalvão, João Paulo; Lima, Renato Abreu (Ciência e Natura, 2018)
Venomous animals are found in a variety of environments, including residential urban areas, which creates a suitable place for reproduction. In this sense, the present work had as objective to understand the approach of the theme of venomous animals in two public schools of the municipality of Benjamin Constant-AM. To that end, students and teachers of basic education working in Primary Education were part of the research, in which structured questionnaires were applied with open and closed questions. In addition, multimedia resources were used for the visual demonstration of concepts, ecological importance, examples, general characteristics and differentiation between venomous and venomous animals. The obtained data were analyzed and tabulated following arithmetic mean between the answers. It was noted that the students involved have a vast knowledge about venomous animals, but that these need to be more worked in a contextualized way facilitating a better understanding of scientific terms, thus improving methods of accident prevention and that these can be multipliers of this knowledge